Geomorphologic evolution of the shallow-buried abandoned Yellow River delta during the last 2000 years - Qing Wang; Lin Zeng; Chao Zhan; Xianbin Liu; Longsheng Wang; Shanshan Cheng; Buli Cui (Frontiers in Marine Science, 2022)
Different from the continuous development of many river deltas since the major Holocene transgression, the modern Yellow River delta (YRD) remained for nearly 1000 years (from 893 AD to 1855 AD) in an abandonment state, until after 1855 AD when it was buried after the Yellow River entered the sea via Lijin. In this study we used optically stimulated luminescence (OSL) dating and grain size and sedimentary facies analysis of four borehole cores, combined with an analysis of landform morphology, to reconstruct the history of the ancient abandoned YRD. The results indicate that after the delta was abandoned due to the reduced sediment supply by the Yellow River in 893 AD, a sandy coast developed under the influence of wave erosion, and offshore shell ridges were formed beyond the coastline. During the interval from the Medieval Warm Period (MWP) to the Little Ice Age (LIA), driven by climate change and storm surges, the shell ridges migrated laterally, widened and rose, while sediment accumulation in the landward-side interfluvial floodplains was relatively weak. This configuration subsequently constituted a coastal highland – plain depression system. After 1077 AD, this system, together with the abandoned delta, was eroded by the Daqing River estuary. After 1855 AD, the abandoned delta landform system was completely buried by Yellow River sediments, and the wave-controlled sandy coast was transformed to a tide-controlled silt-mud coast. We summarize these findings in the form of a geomorphic model of the evolution of the abandoned delta from the MWP to the LIA. Overall, our results highlight the geomorphic effects of the sediment-laden river delta and the response of the abandoned delta geomorphic system on the millennial timescale, and they provide a theoretical foundation for predicting the geomorphic evolution of a major river delta on different timescales, against the background of global change.